Effect of Small-Scale Turbulence on the Physiology and Morphology of Two Bloom-Forming Cyanobacteria - Xiao, Yan (PLoS One, 2016)
The main goal of the present work is to test the hypothesis that small-scale turbulence affected physiological activities and the morphology of cyanobacteria in high turbulence environments. Using quantified turbulence in a stirring device, we conducted one set of experiments on cultures of two strains of cyanobacteria with different phenotypes; i.e., unicellular Microcystis flos-aquae and colonial Anabaena flos-aquae. The effect of small-scale turbulence examined varied from 0 to 8.01×10(−2) m(2)s(-3), covering the range of turbulence intensities experienced by cyanobacteria in the field. The results of photosynthesis activity and the cellular chlorophyll a in both strains did not change significantly among the turbulence levels, indicating that the potential indirect effects of a light regime under the gradient of turbulent mixing could be ignored. However, the experiments demonstrated that small-scale turbulence significantly modulated algal nutrient uptake and growth in comparison to the stagnant control. Cellular N and C of the two stains showed approximately the same responses, resulting in a similar pattern of C/N ratios. Moreover, the change in the phosphate uptake rate was similar to that of growth in two strains, which implied that growth characteristic responses to turbulence may be dependent on the P strategy, which was correlated with accumulation of polyphosphate. Additionally, our results also showed the filament length of A. flos-aquae decreased in response to high turbulence, which could favor enhancement of the nutrient uptake. These findings suggested that both M. flos-aquae and A. flos-aquae adjust their growth rates in response to turbulence levels in the ways of asynchronous cellular stoichiometry of C, N, and P, especially the phosphorus strategy, to improve the nutrient application efficiency. The fact that adaptation strategies of cyanobacteria diversely to turbulence depending on their physiological conditions presents a good example to understand the direct cause—effect relationship between hydrodynamic forces and algae.